PENGARUH PENAMBAHAN PROBIOTIK PADA PAKAN BUATAN TERHADAP PERTUMBUHAN IKAN BAUNG - Jarod Setiaji; Jefri Hardianto; Rosyadi Rosyadi (DINAMIKA PERTANIAN, 2014)
This study was conducted commencing on October 8, 2013 until December 7, 2013, at the hatchery Faculty of Agriculture, University of Islam Riau Pekanbaru. This study aimed to determine the effect of probiotic viterna on artificial feed on fish growth Mystus nemurus. This study used a completely randomized design with 4 treatments: P0 without treatment (control), P1 addition of probiotic viterna 2 cc/kg of feed, P2 4 cc/kg of feed and P3 6 cc/ g of feed. Fish samples used are fish seed baung 2 months old with an average weight of 3.0 g and 6.0 cm long. The container used in this study is the cage net with a size of 1 x 1 x 1.2 (m) 12 units. Analysis of data using analysis of variance with 5% confidence level. The results showed that the addition of probiotic treatment viterna the best feed in the treatment of 6 cc/kg of feed and the addition of probiotic viterna no significant effect on the growth of the absolute weight, daily weight growth rate and feed conversion rate baung fish.